High Entropy Oxide
Patent Information
- Application Number
- JP2024547203
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-06
- Filing Date
- 2023-02-09
- Publication Date
- 2025-03-07
AI Technical Summary
【0100】 本開示のさらなる態様、新規な特色及び利点は、詳細な記載及び図面において示した例示的な実施形態の任意の1つ若しくは複数に鑑みて当業者には容易に明らかである。記載及び図面は本質的に例示的であり、限定的ではないと見なされる。修正又は改善は本開示及び特許請求の範囲の精神又は範囲を逸脱することなく行い得る。
Smart Images

Figure 2025506136000001_ABST
Abstract
Description
[Technical field]
[0001] background Field The present disclosure relates to high entropy oxides, methods for their preparation, and their use as electrode materials and catalysts. [Background technology]
[0002] 2. Description of Related Art High entropy oxides, also known as entropy stabilized oxides, have attracted much attention due to their remarkable compositional and structural stability under extreme conditions, such as extreme temperature and chemical environments. In addition, many other attractive and unique properties have been discovered in these materials, such as exceptional superionic conductivity at room temperature, high dielectric constant, and band gaps that can be tailored to individual requirements. Thus, high entropy oxides can be useful as anode materials (e.g., in lithium batteries), cathode materials, and catalysts.
[0003] Solid-state synthesis is the most common and easiest method to fabricate high entropy oxides. For example, Qiu et al. (Qiu, N.; Chen, H.; Yang, Z.; Sun, S.; Wang, Y.; Cui, Y., “A high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2O) with superior lithium storage performance” Journal of Alloys and Compounds 2019, 777, 767-774) describes a method in which MgO, CoO, NiO, CuO, and ZnO were mixed in a planetary ball mill, then pressed into pellets and sintered at 1000 °C for 24 hours. However, the particles synthesized by the solid-state method are often large, which has a negative impact on the application of entropy-stabilized oxides. For example, large particles tend to slow down the catalytic reaction rate due to the limited specific surface area of the catalyst. A recently developed variation of the solid-state method is to use (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 Atomized spray pyrolysis was used to synthesize ZnO (Sarkar, A.; Velasco, L.; Wang, D.; Wang, Q.; Talasila, G.; de Biasi, L.; Kuebel, C.; Brezesinski, T.; Bhattacharya, SS; Hahn, H., “High entropy oxides for reversible energy storage” Nature communications 2018, 9 (1), 1-9). The entropy-stabilized oxide particles synthesized by this method were found to be hollow or solid spheres, with particle sizes ranging from nanometers to micrometers. Such a wide particle size distribution can result in high applied voltages for large particles when the particles are used as electrode materials.
[0004] Alternatively, co-precipitation methods may be used to synthesize nano-sized high entropy oxides. These methods generally involve converting metal cations into hydroxide precursors and then annealing the precursors to provide oxide products. Sodium hydroxide and ammonia solutions are commonly used to prepare the hydroxide precursors. However, many practical problems arise from these methods. For example, it is difficult to control the shape and size distribution of the synthesized particles because sodium hydroxide and ammonia solutions react rapidly with metal cations. Hexamethylenetetramine (HMTA) or urea may be used as precipitants for uniform deposition, other than direct hydroxide sources, e.g., NaOH. In these cases, the functional component for precipitation is ammonia generated by thermal decomposition of the precipitant, which then dissolves in water to give ammonium hydroxide. The low basicity when stoichiometric ammonia is added allows the Mg 2+ The co-precipitation process usually involves a subsequent annealing process at high temperature. This results in incomplete deposition of Cu(OH)2. On the other hand, excessive addition of urea or HMTA leads to re-dissolution of the as-precipitated Cu(OH)2 by forming copper-ammonia complexes. After co-precipitation, the obtained precursor is usually subjected to a subsequent annealing process at high temperature. Such annealing results in severe agglomeration of ultrafine high-entropy oxide particles. As a result, it is still challenging to synthesize high-entropy oxides with narrow size distribution and uniform composition of submicron particles. Summary of the Invention [Problem to be solved by the invention]
[0005] the purpose It is therefore one object of the present invention to go some way towards avoiding the above disadvantages; and / or to at least provide the public with a useful choice.
[0006] Other objects of the present invention will become apparent from the following description, given by way of example only. [Means for solving the problem]
[0007] overview definition "Annealing process" and "solid solution process" refer to a heat treatment of a material that allows for some degree of atomic movement to reduce structural defects in the material.
[0008] "Caustic process" means a thermal treatment of a material in which the organic components of the material are removed, for example by oxidation or gasification.
[0009] "High entropy oxide" means an oxide material characterized by the presence of four or more elementally distinct metal cations within an ionic structure.
[0010] Oxide materials containing four elementally distinct metal cations may be referred to in the art as "medium entropy oxides." For the avoidance of doubt, in this application, the term "high entropy oxide" encompasses oxide materials characterized by the presence of four or more elementally distinct metal cations within the ionic structure.
[0011] The four or more elementally distinct metal cations are preferably present in substantially equimolar amounts in the high entropy oxide, although this is not required, for example, each metal cation may constitute at least 5% of the total number of the four or more elementally distinct metal cations in the high entropy oxide.
[0012] "Metal cation" includes cations of metal elements in Group 2 (alkaline earth metals) and Groups 3-12 (transition metals).
[0013] "Particle shape" means the shape of a particle. Particle shapes include spheres, rods, cubes, and plates.
[0014] "Particle size D 50 " means the median particle size of the sample.
[0015] "Particle size D 90 " means the 90th percentile particle size of the sample.
[0016] In a first aspect, the present invention is directed to a method for preparing a high entropy oxide, the method comprising: a. providing at least four metal salts; b. mixing a metal salt in a solvent to form a solution; c. mixing the solution obtained in step (b) with a precipitant to obtain a precipitate; d. heat treating the precipitate of step (c) to obtain a high entropy oxide; Includes.
[0017] In some embodiments, the heat treating step (d) comprises heating the precipitate for a period of at least about 30 minutes, hi some embodiments, the heat treating comprises heating the precipitate for a period of about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, or about 8 hours.
[0018] In some embodiments, the heat treatment of step (d) comprises a calcination process. In some embodiments, the calcination process is carried out at a temperature between about 300° C. and about 1200° C. In some embodiments, the calcination process is carried out at a temperature between about 350° C. and about 450° C. In some embodiments, the calcination process is carried out at a temperature between about 400° C. In some embodiments, the calcination process is carried out at a temperature between about 900° C. and about 1100° C. In some embodiments, the calcination process is carried out at a temperature of about 1000° C.
[0019] In some embodiments, the heat-treating step (d) comprises a calcination process to provide an oxide intermediate, hi some embodiments, the calcination process comprises heating the precipitate at a temperature between about 300° C. and about 500° C. for a period of about 2 hours to about 4 hours to form the oxide intermediate.
[0020] In some embodiments, the heat treating step (d) comprises an annealing process. In some embodiments, the annealing process comprises heating the intermediate oxide at a temperature between about 900° C. and about 1100° C. for a period of about 3 hours to about 6 hours ... for a period of at least 5 hours.
[0021] In some embodiments, the heat treatment step (d) comprises an annealing process that is carried out immediately after the calcination process, for example in the same apparatus, without isolating the oxide intermediate. In some embodiments, the oxide intermediate is cooled (e.g., to room temperature) prior to the annealing process.
[0022] In some embodiments, the heat treating step (d) comprises a combined calcination and annealing process that comprises heating the precipitate at a temperature between about 900° C. and about 1100° C. for a period of time between about 3 hours and about 6 hours.
[0023] In some embodiments, the oxide intermediate is mixed with a solid-state dispersant prior to annealing. In some of these embodiments, the oxide intermediate is suspended in a solvent (e.g., water) together with the solid-state dispersant, and then the suspension is dried and the resulting powder is ground prior to annealing.
[0024] In some embodiments, the amount of solid-state dispersant is greater than about 5 times (by weight) the amount of oxide intermediate. In some embodiments, the amount of solid-state dispersant is greater than about 10 times (by weight) the amount of oxide intermediate. In some embodiments, the amount of solid-state dispersant is about 5 to about 15 times (by weight) the amount of oxide intermediate. In some embodiments, the amount of solid-state dispersant is about 10 times (by weight) the amount of oxide intermediate.
[0025] In some embodiments, the solid-state dispersant is a material with a melting point above the annealing temperature. In some embodiments, the solid-state dispersant is water-soluble. In some embodiments, the solid-state dispersant is inert. Preferably, the solid-state dispersant is selected from the group consisting of potassium sulfate, potassium phosphate, sodium phosphate, sodium aluminate, and combinations of any two or more thereof. In some embodiments, the solid-state dispersant is potassium sulfate.
[0026] In some embodiments, the method further comprises washing the product from the annealing process involving the solid-state dispersant with water to remove the solid-state dispersant.
[0027] In some embodiments, the solid-state dispersant is selected from the group consisting of potassium sulfate, potassium phosphate, sodium phosphate, sodium aluminate, and combinations of any two or more thereof, hi some embodiments, the solid-state dispersant is potassium sulfate.
[0028] In some embodiments, the heat-treating step (d) comprises the use of a controlled atmosphere, hi some embodiments, the controlled atmosphere comprises oxygen.
[0029] In some embodiments, four metal salts are provided in step (a). In some embodiments, five metal salts are provided. In some embodiments, six or more metal salts are provided.
[0030] In some embodiments, the metal salts are selected from the group consisting of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt salts, in some embodiments, the metal salts are each independently selected from a chloride salt, a nitrate salt, a sulfate salt, or an acetate salt.
[0031] In some embodiments, the metal salts are salts of Mg, Ni, Cu, Co, and Zn. In some embodiments, the Mg, Co, Ni, and Cu salts are each independently selected from a chloride, a nitrate, a sulfate, or an acetate. In some embodiments, the Mg, Co, Ni, and Cu salts are chloride salts. In some embodiments, the Zn salt is a nitrate, a sulfate, or an acetate. In some embodiments, the Zn salt is a nitrate.
[0032] In some embodiments, the metal salts are Mg, Mn, Fe, Co, and Ni salts. In some embodiments, the Mg, Co, Ni, and Cu salts are each independently selected from chloride, nitrate, sulfate, or acetate salts. In some embodiments, the Mg, Mn, Fe, Co, and Ni salts are chloride salts.
[0033] In some embodiments, the precipitating agent is a hydroxide compound (e.g., NaOH), an organic compound (e.g., an oxalate compound), or a source of ammonia (e.g., hexamethylenetetramine or urea). A preferred precipitating agent is an oxalate compound. In some embodiments, the oxalate compound is soluble in a solution of water and ethylene glycol, for example, a 1:2 water:ethylene glycol solution (by volume). In some embodiments, the oxalate compound is ammonium oxalate. In some embodiments, the oxalate compound is ammonium oxalate monohydrate.
[0034] In some embodiments, the solvent used in step (b) to form the solution of metal salt is water, e.g., deionized water; water and an organic solvent; or an organic solvent. A preferred solvent includes water and ethylene glycol. In some embodiments, the solvent includes a mixture of water and ethylene glycol, where the water and ethylene glycol are in a ratio (by volume) ranging from 1.5:2 to 0.5:2. In some embodiments, the solvent includes water and ethylene glycol in a ratio (by volume) of about 1:2.
[0035] The four or more elementally different metal cations are preferably present in substantially equimolar amounts, although this is not required. In some embodiments, the amount of each of the metal cations is at least about 5% of the total amount of metal cations. Each metal cation may constitute at least 10%, at least 15%, at least 20%, or at least 25% of the total number of metal cations in the high entropy oxide. Each metal cation in the high entropy oxide may constitute 5% to 30% of the total number of metal cations in the high entropy oxide. For example, each metal cation in the high entropy oxide may constitute 10% to 30%, or 15% to 30%, or 20% to 30% of the total number of metal cations.
[0036] In some embodiments, the precipitating agent is dissolved in a solvent prior to mixing with the solution obtained in step (b). In some embodiments, the solvent used to dissolve the precipitating agent is water. In some embodiments, the solvent comprises a mixture of water and an organic solvent, such as ethylene glycol. In some embodiments, the solvent comprises a mixture of water and ethylene glycol, where the water and ethylene glycol are in a ratio (by volume) ranging from 1.5:2 to 0.5:2. In some embodiments, the solvent comprises water and ethylene glycol in a ratio (by volume) of about 1:2.
[0037] In some embodiments, the precipitation in step (c) is obtained in a solvent comprising water, e.g., deionized water; water and an organic solvent; or an organic solvent. In some embodiments, the solvent comprises a mixture of water and ethylene glycol, the mixture in a ratio (by volume) ranging from 1.5:2 to 0.5:2. In some embodiments, the solvent comprises water and ethylene glycol in a ratio (by volume) of about 1:2.
[0038] In some embodiments, the high entropy oxide has an entropy stabilized crystal structure.
[0039] In another aspect, the present invention is directed to a high entropy oxide prepared by the method of the present invention.
[0040] In another aspect, the present invention is directed to a method for controlling the particle size dispersity of a high entropy oxide, wherein using the above method for preparing a high entropy oxide, the heat treatment in step (d) is carried out at a controlled temperature and / or time to produce a desired particle size dispersity.
[0041] In another aspect, the present invention provides a compound represented by the formula (A v B w C x D y E z )O, wherein v, w, x, y, and z are each independently between about 0.05 and about 0.30, with the proviso that v+w+x+y+z=1; and each of A, B, C, D, and E is a different element selected from the list consisting of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt; wherein the high entropy oxide is characterized by any one or more of the following: X-ray powder diffraction spectrum containing (111) and (200) peaks, where I (111) / I (200) The relative peak intensity of is greater than about 1; Average particle size D of about 800 nm or less 50 ; Particle size D of about 1200 nm or less 90 ; Submicron particles with rod-like shape; Particle size distribution with a standard deviation of less than about 250 nm.
[0042] In some embodiments, v, w, x, y, and z are each about 0.2.
[0043] In some embodiments, the high entropy oxide has the formula (Mg v Co w Ni x Cu y Zinc z )O, or formula (Mg v Mn w Fe x Co y Niz )O.
[0044] In some embodiments, I (111) / I (200) The relative peak intensity of I is about 1.2 to about 2.0, about 1.3 to about 1.9, about 1.4 to about 1.8, or about 1.5 to about 1.7. (111) / I (200) The relative peak intensity of is about 1.6.
[0045] In some embodiments, the high entropy oxide is characterized by an X-ray powder diffraction spectrum that includes (111), (200), and (220) peaks. (220) / I (200) The relative peak intensity of I is about 0.3 to about 1.1, about 0.4 to about 1.0, about 0.5 to about 0.9, or about 0.6 to about 0.8. (20) / I (200) The relative peak intensity of is 0.7.
[0046] In some embodiments, the high entropy oxide is characterized by an X-ray powder diffraction spectrum that includes (111), (200), (220), (311), and (222) peaks. (311) / I (222) The relative peak intensity of is less than about 1.
[0047] In some embodiments, the high entropy oxide is characterized by an X-ray powder diffraction spectrum substantially as shown in FIG.
[0048] In some embodiments, the high entropy oxide is characterized as having a substantially uniform particle size distribution.
[0049] In some embodiments, the high entropy oxide has a particle size distribution with a standard deviation of less than about 245 nm, less than about 240 nm, less than about 235 nm, less than about 230 nm, less than about 225 nm, less than about 220 nm, less than about 215 nm, less than about 210 nm, less than about 205 nm, or less than about 200 nm. In some embodiments, the high entropy oxide has a particle size distribution with a standard deviation of about 215 nm and a relative standard deviation of about 0.34.
[0050] In some embodiments, the high entropy oxide has an average particle size D of about 700 nm or less. 50 In some embodiments, the high entropy oxide has an average particle size D of about 600 nm or less. 50 In some embodiments, the high entropy oxide has an average particle size D of about 600 nm. 50 In some embodiments, the high entropy oxide has a particle size D of about 1100 nm or less. 90 In some embodiments, the high entropy oxide has a particle size D of about 1000 nm or less. 90 In some embodiments, the high entropy oxide has a particle size D of about 1000 nm. 90 It is characterized by:
[0051] In some embodiments, the submicron particles having a rod-like shape have a length:width ratio of about 1:1.5 to about 1:3.5. In some embodiments, the submicron particles have a length:width ratio of about 1:2 to about 1:3. In some embodiments, the submicron particles have a length:width ratio of about 1:2.5. In some embodiments, the submicron particles have an average length of about 400 nm to about 1000 nm. In some embodiments, the submicron particles have an average length of about 500 nm to about 900 nm. In some embodiments, the submicron particles have an average length of about 630 nm. In some embodiments, the submicron particles have an average width of about 150 nm to about 450 nm, about 200 nm to about 400 nm, or about 250 nm to about 350 nm. In some embodiments, the submicron particles have an average width of about 300 nm.
[0052] In some embodiments, the high entropy oxide is substantially non-porous.In some embodiments, the high entropy oxide is non-porous.
[0053] In some embodiments, the high entropy oxide is substantially homogeneous, hi some embodiments, the high entropy oxide is single phase.
[0054] In some embodiments, the high entropy oxide has a lattice constant of at least about 4 Å, preferably about 4.0 Å to about 4.4 Å, more preferably about 4.1 Å to about 4.3 Å. In some embodiments, the lattice constant is about 4.24 Å, preferably the lattice constant is 4.2395 Å.
[0055] In yet another aspect, the present invention is directed to an electrode, such as an anode or cathode, comprising a high entropy oxide according to the present invention.
[0056] In some embodiments, the electrode comprises at least about 70% (by weight) high entropy oxide. In some embodiments, the electrode comprises at least about 80% (by weight) high entropy oxide. In some embodiments, the electrode comprises about 80% (by weight) high entropy oxide.
[0057] In some embodiments, the electrode is an anode. In some embodiments, the anode further comprises a conductive additive, such as carbon black (e.g., Super P carbon black), acetylene black, conductive graphite, Ketjen black™, carbon nanotubes, or a combination of any two or more thereof. In some embodiments, the anode comprises about 5% to about 15% (by weight) of the conductive additive. In some embodiments, the anode comprises about 10% (by weight) of the conductive additive. In some embodiments, the anode further comprises a binder, such as polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), or a combination thereof. In some embodiments, the anode comprises about 5% to about 15% (by weight) of the binder. In some embodiments, the anode comprises about 10% (by weight) of the binder. In some embodiments, the anode further comprises another anode material.
[0058] In some embodiments, the anode has a nominal capacity of at least about 600 mAh / g. In some embodiments, the anode has a nominal capacity of about 600 mAh / g to about 1200 mAh / g. In some embodiments, the anode has a nominal capacity of at least about 700 mAh / g, about 800 mAh / g, about 900 mAh / g, about 100 mAh / g, about 1100 mAh / g, or about 1200 mAh / g. In some embodiments, the anode has a nominal capacity of about 800 mAh / g at a charge / discharge rate of 0.2 A / g. In some embodiments, the anode has a nominal capacity of at least about 800 mAh / g after 400 cycles. In some embodiments, the anode has a nominal capacity of at least about 900 mAh / g after 400 cycles. In some embodiments, the anode has a nominal capacity of at least about 1000 mAh / g after 400 cycles. In some embodiments, the anode has a specified capacity of at least about 1100 mAh / g after 400 cycles. In some embodiments, the anode has a specified capacity of at least about 800 mAh / g after 470 cycles. In some embodiments, the anode has a specified capacity of at least about 900 mAh / g after 470 cycles. In some embodiments, the anode has a specified capacity of at least about 1000 mAh / g after 470 cycles. In some embodiments, the anode has a specified capacity of at least about 1100 mAh / g after 470 cycles.
[0059] In yet another aspect, the present invention is directed to a catalyst comprising the high entropy oxide according to the present invention. In some embodiments, the catalyst is useful for catalyzing a reaction selected from the group consisting of water gas shift, steam reforming, Fischer-Tropsch synthesis from CO2 reduction, or higher alcohol synthesis.
[0060] In a further aspect, the present invention is directed to an electrochemical cell comprising an anode, a cathode, a separator between the anode and the cathode, and an electrolyte, wherein the anode comprises a high entropy oxide according to the present invention.
[0061] In some embodiments, the electrochemical cell is included in a lithium-ion battery.
[0062] In a further embodiment, a high entropy oxide is provided comprising four or more elementally distinct metal cations, each metal cation constituting at least 5% of the total number of the four or more elementally distinct metal cations in the high entropy oxide, wherein the high entropy oxide comprises a rod-like particle shape.
[0063] The high entropy oxide may include five elementally distinct metal cations.
[0064] Each metal cation in the high entropy oxide may constitute at least 10%, at least 15%, at least 20%, or at least 25% of the total number of metal cations in the high entropy oxide. Each metal cation in the high entropy oxide may constitute between 5% and 30% of the total number of metal cations in the high entropy oxide.
[0065] Each metal cation may be present in substantially equimolar amounts.
[0066] Each metal cation may be independently selected from the group consisting of cations of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt.
[0067] The high entropy oxide may be characterized by one or more of the following: a particle size D50 of about 800 nm or less; and a particle size D90 of about 1200 nm or less.
[0068] The high entropy oxide may be characterized by a particle size distribution having a standard deviation of less than about 250 nm.
[0069] The high entropy oxide has the formula (Mg v Co w Ni x Cu y Zinc z )O or (Mg v Mnw Fe x Co y Ni z )O, where v, w, x, y, and z are between 0.05 and 0.30. In some embodiments, v, w, x, y, and z can each be between 0.05 and 0.30, between 0.1 and 0.3, between 0.15 and 0.25, or about 0.2.
[0070] High entropy oxides can be characterized by an X-ray powder diffraction spectrum containing (111) and (200) peaks, where the relative peak intensity of I(111) / I(200) is greater than about 1.
[0071] The high entropy oxide may be characterized by an X-ray powder diffraction spectrum containing (111), (200) and (220) peaks, with the relative peak intensity of I(220) / I(200) being from about 0.3 to about 1.1.
[0072] The high entropy oxide may be characterized by an X-ray powder diffraction spectrum containing (111), (200), (220), (311) and (222) peaks, with the relative peak intensity of I(311) / I(222) being less than about 1.
[0073] The length:width ratio of the submicron particles of the high entropy oxide can be from about 1:1.5 to about 1:3.5.
[0074] In a further aspect, a method for preparing a high entropy oxide is provided, the method comprising: (a) mixing a solution comprising at least four elementally distinct metal cations in a solvent, where each metal cation constitutes at least 5% of the total number of the four or more elementally distinct metal cations, with a precipitating agent to obtain a solid material comprising at least four metal cations; and (b) heat treating the solid material to obtain a high entropy oxide; wherein the precipitating agent comprises an organic anion.
[0075] The heat treatment may include a calcination process to produce a high entropy oxide intermediate.
[0076] The heat treatment may also include the use of a controlled atmosphere, which contains a controlled amount of oxygen.
[0077] The method may include annealing the high entropy oxide intermediate to obtain the high entropy oxide.
[0078] The method may include mixing the high entropy oxide intermediate with a solid-state dispersant prior to annealing.
[0079] The high entropy oxide may be quenched following annealing. The high entropy oxide may be quenched by rapidly cooling the high entropy oxide immediately after the annealing process. Quenching may be accomplished by removing the high entropy oxide from the oven and cooling by exposure to ambient (e.g., room temperature) air. Quenching may also be accomplished by contacting the high entropy oxide with a chilled fluid, such as chilled air or liquid nitrogen.
[0080] The solution may include at least five elementally different metal cations.
[0081] Each metal cation may be independently selected from the group consisting of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt cations. For example, each metal cation may be independently selected from the group consisting of Mg, Co, Ni, Cu, and Zn cations, or may be independently selected from the group consisting of Mg, Mn, Fe, Co, and Ni cations.
[0082] The precipitating agent can include oxalate anions. For example, the precipitating agent can include ammonium oxalate.
[0083] The solvent may include water, a combination of water and an organic solvent, or an organic solvent. The solvent may include water and ethylene glycol, for example, water and ethylene glycol in a ratio (by volume) ranging from 1.5:2 to 0.5:2.
[0084] In a further aspect, there is provided a method for preparing a high entropy oxide, the method comprising: a. mixing a solution comprising at least four elementally distinct metal cations in a solvent, each metal cation constituting at least 5% of the total number of the four or more elementally distinct metal cations, with a precipitating agent to obtain a solid material comprising at least four metal cations; b. heat treating the solid material to obtain a high entropy oxide intermediate; c. mixing the high entropy oxide intermediate with a solid-state dispersant and annealing the high entropy oxide intermediate to form a high entropy oxide; Includes.
[0085] In a further embodiment, an oxalate salt is provided that comprises four or more elementally distinct metal cations, each metal cation making up at least 5% of the total number of metal cations.
[0086] The oxalate salt may comprise or consist essentially of particles each containing four or more elementally distinct metal cations.
[0087] Each metal cation may be independently selected from the group consisting of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt cations. For example, each metal cation may be independently selected from the group consisting of Mg, Co, Ni, Cu, and Zn cations, or may be independently selected from the group consisting of Mg, Mn, Fe, Co, and Ni cations.
[0088] The oxalate may be a solid material having a submicron particle size. The oxalate may have a rod-like shape. For example, the length:width ratio of the oxalate particles may be about 1:1.5 to about 1:3.5.
[0089] Oxalates are represented by the formula (A v B w C x D y E z)C2O4, where v, w, x, y, and z are each independently about 0.05 to about 0.30, and A, B, C, D, and E are each independently selected from the group consisting of cations Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb, and Pt. In some embodiments, v, w, x, y, and z can each be 0.05 to 0.30, 0.1 to 0.3, 0.15 to 0.25, or about 0.2.
[0090] In a further aspect, there is provided a method of preparing the above oxalate salt comprising combining a first solution containing four or more elementally distinct metal cations, each metal cation constituting at least 5% of the total number of metal cations in the solution, with a stoichiometrically equivalent amount of oxalate anion.
[0091] Four or more elementally different metal cations may be present in each oxalate particle in their stoichiometric ratio.
[0092] In a further embodiment, the compound of formula (Mg v Mn w Fe x Co y Ni z )O, where v, w, x, y, and z can be 0.05 to 0.30, 0.1 to 0.3, 0.15 to 0.25, or about 0.2, respectively.
[0093] The invention may also be broadly stated to consist in any or all combinations of the parts, elements and features referred to or indicated in the specification of this application, individually or collectively, and any two or more of said parts, elements or features, where a particular integer having a known equivalent in the art to which the invention pertains is set forth herein, and such known equivalents are deemed to be incorporated herein as if individually set forth.
[0094] Furthermore, when features or aspects of the invention are described in terms of a Markush group, those of skill in the art will recognize that the invention is also thereby described in terms of any individual members or subgroups of members of the Markush group.
[0095] As used herein, "(s)" following a noun refers to the plural and / or singular form of the noun.
[0096] As used herein, the term "and / or" means "and" or "or" or both.
[0097] The term "comprising", as used herein, means "consisting at least in part of." When interpreting each statement in this specification that includes the term "comprising," features other than those beginning with this term may also be present. Related terms, such as "comprise" and "include," are to be interpreted in the same manner.
[0098] Reference to a numerical range disclosed herein (e.g., 1-10) is also intended to incorporate reference to all rational numbers within that range (e.g., 1, 1.1, 2, 3, 3.9, 4, 5, 6, 6.5, 7, 8, 9, and 10) and also to any range of rational numbers within that range (e.g., 2-8, 1.5-5.5, and 3.1-4.7), and thus all subranges of all ranges expressly disclosed herein are hereby expressly disclosed. These are merely examples of what is specifically intended, and all possible combinations of numerical values between the lowest and highest values recited are considered to be expressly described in this application in a similar manner.
[0099] While the invention is broadly as defined above, those skilled in the art will recognize that the invention is not so limited and that the invention also includes embodiments of which the following description provides examples.
[0100] Further aspects, novel features and advantages of the present disclosure will be readily apparent to those skilled in the art in view of any one or more of the exemplary embodiments set forth in the detailed description and drawings. The description and drawings are to be regarded as illustrative in nature and not restrictive. Modifications or improvements may be made without departing from the spirit or scope of the disclosure and claims.
[0101] Brief description of some figures of the drawing Some example embodiments will now be described, by way of example, with reference to the accompanying drawings in which: [Brief description of the drawings]
[0102] [Figure 1a] 1 shows an SEM image of the as-precipitated oxalate precursor described in Example 1. [Figure 1b] 6 shows TEM bright field images of several oxalate precursor bundles described in Example 1. [Figure 2a] FIG. 1 shows a high angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of the oxalate bundles described in Example 1 with a scale bar of 200 nm. [Figure 2b] Each shows EDS elemental mapping of Cu. [Figure 2c] Each shows EDS elemental mapping of Co. [Figure 2d] Each shows EDS elemental mapping of Ni. [Figure 2e] Each shows EDS elemental mapping of Zn. [Figure 2f] Each shows EDS elemental mapping of Mg. [Diagram 3] 1 shows thermogravimetry (TGA), differential scanning calorimetry (DSC), and derivative thermogravimetry (DTG, dotted line) plots of the oxalate precursor described in Example 1. [Figure 4]Figure 1 shows XRD patterns of high entropy oxides annealed from room temperature to different final temperatures and then held at each temperature for 3 hours as described in Example 2. From bottom to top: 700°C, 800°C, 900°C, and 1000°C. Squares, asterisks, triangles, and sharps indicate halite, tenorite (CuO), spinel (Co3O4), and wurtzite (ZnO) phases, respectively. [Diagram 5] Figure 1 shows the XRD pattern of high-entropy oxide (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O prepared by solid-state dispersion-assisted annealing. The projections of different crystal planes are shown next to their corresponding diffraction peaks. [Figure 6] The Rietveld refinement of the corresponding XRD pattern is shown. [Figure 7a] 1 shows an SEM image of a high entropy oxide rod. [Figure 7b] A bright field TEM image of high entropy oxide rods is shown. [Figure 7c] A high-resolution TEM image of a high-entropy oxide rod showing (111) rock-salt lattice fringes in the plane parallel to the longitudinal axis of the rod (while the inset in the upper left corner is the corresponding FFT pattern). [Figure 8a] A HAADF-STEM image (metal cations and oxygen anions are shown as large and small spheres, respectively) is shown. [Figure 8b] An ABF image (metal cations and oxygen anions are shown as large and small spheres, respectively) is shown. [Figure 8c]
[0100] A contrast-reversed image of an ABF image taken along the orientation (metal cations and oxygen anions are shown as large and small spheres, respectively) is shown. [Figure 8d]
[0110] An ABF image taken along the orientation (drift of O atom columns is shown as an arrow, the direction of the arrow indicates the drift orientation) is shown. [Figure 9a] The CV curves for the first five cycles are shown. [Figure 9b]CV curves at half-moon scan rates from 0.3 mV / s to 1.0 mV / s are shown. [Figure 9c] Voltage profiles at different cycles at a charge / discharge rate of 0.2 A / g are shown. [Figure 10] 1 shows the cycling performance of a high entropy oxide anode at 0.2 A / g for 470 cycles. [Figure 11a] Shows speed performance. [Figure 11b] 4 shows the voltage profiles at different charge and discharge rates. [Figure 11c] Figure 2 shows the cycling performance of a conventionally annealed (CA) high-entropy oxide anode at 0.1·A / g. [Figure 12] The first discharge profiles of high-entropy oxide anodes prepared by conventional annealing (dotted line) and dispersant-assisted annealing (solid line) at a charge-discharge rate of 0.1 A / g are shown, and the inset is the differential capacity plot (dQ / dV) of the two discharge profiles. [Figure 13a] Figure 2 shows the XRD pattern of the product annealed without external oxygen. [Figure 13b] 4 shows the XRD pattern of the product annealed with excess oxygen. [Figure 13c] 1 shows the XRD pattern of the product annealed with external oxygen and insufficient annealing time. [Figure 13d] 13 shows the XRD pattern of the product of full annealing and external oxygen according to Example 6. [Figure 14] FIG. 1 shows an SEM image of the as-precipitated oxalate precursor described in Example 5. [Figure 15] 1 shows the oxidation states of Mn, Fe, Co, and Ni in the high entropy oxide of Example 6, as investigated by X-ray absorption near edge structure (XANES). [Figure 16] 1 illustrates one aspect of the subject matter in accordance with one embodiment. [Figure 17a] High angle annular dark-field scanning transmission electron microscope (HAADF-STEM) images (scale bar of 100 nm) are shown. [Figure 17b] 13 shows EDS elemental mapping of Mg(b) for the high entropy oxide particles described in Example 6. [Figure 17c] 13 shows EDS elemental mapping of Mn(c) for the high entropy oxide particles described in Example 6. [Figure 17d] 13 shows EDS elemental mapping of Fe(d) for the high entropy oxide particles described in Example 6. [Figure 17e] 13 shows EDS elemental mapping of Co(e) for the high entropy oxide particles described in Example 6. [Fig. 17f] 13 shows EDS elemental mapping of Ni(f) for the high entropy oxide particles described in Example 6. [Figure 18] FIG. 1 shows a schematic diagram of the half-cell described in Example 3. [Figure 19] FIG. 1 shows a schematic diagram of a coin cell as described in Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0103] Detailed Description Working Example Characterization method The composition of the samples was determined by ICP optical emission spectroscopy (ICP-OES Agilent 5110). Approximately 10 mg of each sample was dissolved in 10 ml of aqua regia at 200 °C in a PTFE beaker. The analysis was performed using five different calibration solutions. The structure and phase purity of the different samples were characterized by X-ray diffraction (X'Pert Pro MPD with Cu Kα radiation). Thermal analysis was performed on a simultaneous thermal analyzer (Netzsch STA 449 F3 Jupiter) with a ramp rate of 5 °C / min in air flow in Pt crucibles. X-ray photoelectron spectroscopy measurements were performed on a Thermo Escalab 250 XI with a monochromated Al Kα source and a spot size of 400 μm. All spectra were calibrated with the C1s peak of exogenous hydrocarbons at 284.8 eV before fitting.
[0104] SEM images were taken on a field emission scanning electron microscope (Thermo Fisher Scientific Apreo S) operating at 30 kV and 0.4 nA. Bright-field TEM images and EDS line scans were obtained on a transmission electron microscope (FEI Tecnai F30) equipped with an XFlash 6T-60 EDS detector (Bruker). Atomic-scale characterization of individual high-entropy oxide nanorods was performed on an aberration-corrected S / TEM (FEI Titan Cubed Themis G2 300, FEI) at an accelerating voltage of 300 kV with a convergence half angle of 25 mrad. The S / TEM was equipped with a monochromator, an EDS detector (Bruker), a Gatan imaging filter for a high-resolution electron energy loss spectrometer (GIF Quantum ER / 965, Gatan), and a high-speed K2 camera (Gatan). The multiple inelastic scattering background in the core-loss region was removed by Fourier ratio deconvolution of the low energy loss signal. Line profiles were collected from the EDS mapping of each elemental cation using Gatan DigitalMicrograph GMS3 software. Profiles were converted to text files via a script (export profiles as tab-delimited text) generated by Dave Mitchell, available on the website: www.dmscripting.com.
[0105] All chemicals were purchased from Sigma Aldrich and used without further purification. EXAMPLES
[0106] Example 1a: (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 )O Coprecipitation of Oxalate Precursors of High-Entropy Oxides High entropy oxide ((Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc0.2 A preferred method for the generation of precursors for forming Cr(O) involved the use of oxalate anion to achieve near equimolar deposition of elementally distinct cations by forming corresponding complexes in solution. The oxalate anion was found to form precipitating complexes with Mg, Co, Ni, Cu, and Zn cations in polar, protic solutions. The oxalate anion was particularly preferred because it was found to have similar rates of precipitate formation for each metal cation such that each precipitate particle contained a proportion of metal cation that was substantially equivalent to the proportion of metal cations in the reaction solution.
[0107] MgCl2·6H2O (99%, 0.55 mmol), CuCl2·6H2O (99%, 0.5 mmol), CoCl2·6H2O (99%, 0.5 mmol), NiCl2·6H2O (99.9%, 0.5 mmol), and Zn(NO3)2·6H2O (98%, 0.5 mmol) were dissolved in a mixture of 10 ml of deionized water and 20 ml of ethylene glycol, marked as solution A. Zinc nitrate was the preferred zinc source. Zinc chloride is less preferred as a zinc source because it forms insoluble zinc oxychloride in aqueous solution. Excess magnesium chloride was added because magnesium oxalate precipitate is slightly soluble. Ammonium oxalate monohydrate ((NH4)2C2O4·H2O, 99%, 2.55 mmol) was then dissolved in another mixed solution of 10 ml deionized water and 20 ml ethylene glycol marked as solution B at 50 °C. Ammonium oxalate was the preferred precipitant due to its solubility in the water:ethylene glycol solvent. When compared to oxalate salts, the precipitation of metal cations was less uniform when oxalic acid was used (without being bound by theory, this may be due to the acidity of oxalic acid affecting the relative solubility of metal cations in solution). Group I counterions, e.g., sodium oxalate, are insoluble in ethylene glycol, and oxalic acid may cause dissolution of the oxalate that remains precipitated. Both solutions A and B were heated to 50 °C with stirring. Solution B (oxalate ions) was then rapidly poured into solution A (metal ions) with vigorous stirring. The suspension was further stirred at 50° C. for 8 h, followed by separation of the oxalate precursor from the reaction solution by centrifugation. The precursor was washed several times with water and absolute ethanol, and then dried at 70° C. overnight.
[0108] Without wishing to be bound by theory, the inventors believe that the complexes are formed in a stepwise polymerization. The copper-oxalate complex is formed first, followed by the other three transition metal ions (i.e., Ni 2+ , Zn 2+ , and Co 2+ ) complex was formed. The low value of the critical stability constant (log K) indicates that Mg 2+The cation has the greatest difficulty in coordinating with the oxalate ion. Therefore, the chains of magnesium-oxalate complexes were formed last. This process resulted in the precipitated oxalate precursors with rod-like shapes and hierarchical bundle structures.
[0109] Figure 1(a) illustrates a scanning electron microscope (SEM) image of the as-prepared oxalate precursor. The precursor precipitated by the above process exhibited a bundle-like structure. The transmission electron microscope (TEM) image in Figure 1(b) shows that the oxalate bundles were monodispersed. Each bundle was 500 nm to 1 μm long and had a size of 180 × 180 nm. 2 The TEM images also revealed that the as-precipitated precursor was dense and solid. Energy dispersive X-ray spectroscopy (EDS) analysis was performed on one of these bundles. The Cu signal was stronger at the center. In contrast, the Mg signal was relatively stronger on the periphery of the bundle. The Ni, Zn, and Co signals were almost uniform throughout the oxalate bundle. Thus, the results of the EDS analysis substantiated the above hypothesis about the hierarchical structure.
[0110] Figure 2a shows a high angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of the oxalate bundle. In Figures 2(b)-(f), elemental mapping of Cu, Co, Ni, Zn, and Mg are shown separately. At first glance, the overall distribution of the five metal cations throughout the bundle suggests successful co-precipitation of multicomponent systems at the submicron scale. Furthermore, detailed observation shows that Mg concentrations were stronger on the periphery, while those of Cu were denser in the core (see Figures 2(b) and 2(f)).
[0111] The chemical composition of the oxalate precursor was further determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). The results showed that the molar percentages of each metal cation were relatively close to 20%, i.e., they were close to equimolar.
[0112] Example 1b: Alternative Anions Several alternative anions were investigated for the preparation of high entropy oxide precursor materials. These included hydroxide, formate, acetate, and citrate. The method of Example 1a was followed, except that oxalate was used in place of the stoichiometric equivalents of sodium hydroxide, ammonium hydroxide, hexamethylenetetramine, formate, acetate, and citrate. Comments on the suitability of these anions are provided in Table 1 below.
[0113] [Table 1]
[0114] [Table 2]
[0115] Example 2: (Mg) from an oxalate precursor 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 Calcination and high temperature annealing of )O To prepare the oxide intermediates, the dried oxalate precursors were calcined in a muffle furnace at 400° C. for 3 h with a ramp rate of 10° C. / min.
[0116] The calcined oxide intermediates were treated to form high entropy oxides using two different annealing approaches.
[0117] In the typical approach, the oxide intermediate (as-calcined, appearing as a black powder) was annealed in a muffle furnace at different temperatures for 3 h. The temperatures used were 700° C., 800° C., 900° C. and 1000° C. The ramp rate for all processes was 10° C. / min.
[0118] The second approach was an annealing process assisted by solid-state dispersants. 0.2 g of oxide intermediate was redispersed in 40 ml of deionized water with 2 g of K2SO4 for 30 min under stirring. After sonication for 20 min, the suspension was placed in an oven and heated to 120 °C. After complete removal of water, the solid product was pulverized in a mortar. The powder was subsequently placed in a ceramic crucible and annealed at 1000 °C for 3 h with the same ramp rate as used previously. After annealing, K2SO4 was dissolved in water while the solid product was isolated by vacuum filtration. Particles of high entropy oxide with rod-like shape were obtained, after which the product was washed with appropriate deionized water and the sample was dried in an oven.
[0119] The high entropy oxide may be quenched following annealing. The high entropy oxide may be quenched by rapidly cooling the high entropy oxide immediately after the annealing process. Quenching may be accomplished by removing the high entropy oxide from the oven and cooling by exposure to ambient (e.g., room temperature) air. Quenching may also be accomplished by contacting the high entropy oxide with a chilled fluid, such as chilled air or liquid nitrogen.
[0120] Excellent particle size distribution and uniformity, as well as excellent electrochemical performance, were obtained by an annealing process for at least 5 hours.
[0121] Thermogravimetry (TG) analysis of the high entropy oxide in air from 30 to 1000 °C at a ramp rate of 5 °C / min showed two significant weight loss steps between 100 and 400 °C (Figure 3). The weight loss at lower temperatures, represented by an inflection point at 169 °C in differential thermogravimetry (DTG), corresponds to water loss. The weight loss at higher temperatures corresponds to the decomposition of the oxalate precursor, represented by an inflection point at about 326 °C in DTG. At 1000 °C, roughly 38% of the mass remains as high entropy products. Differential scanning calorimetry (DSC) further confirms that the water loss process is endothermic, while the decomposition of the oxalate is exothermic. Additionally, a very large endothermic peak located at 740 °C is observed. This peak corresponds to the incorporation of Zn into the rock salt structure. 2+ Figure 4 shows an entropy-driven solid solution process involving the incorporation of oxalate and the conversion of spinel Co3O4 to CoO. The mixing of various components at submicron or even nanometer scale in the oxalate precursor is believed to facilitate the solid solution process at a lower annealing temperature compared to known processes. Furthermore, according to the X-ray diffraction (XRD) pattern in Figure 4, Bragg peaks indicative of tenorite CuO can be observed after heating the precursor at 800°C for 3 hours. As tenorite CuO is gradually incorporated into the rock salt structure, those peaks disappear after further increasing the temperature to above 900°C, which is consistent with the slight endothermic peak in the DSC curve centered at 830°C.
[0122] Regular annealing at 1000°C can result in severe aggregation of particles. Therefore, to avoid the formation of large aggregates, a solid-state dispersant was used during high-temperature annealing. Without being bound by theory, it is believed that the solid-state dispersant inhibits aggregation and crystallite growth. Considering that the annealing temperature can be as high as 1000°C, potassium sulfate was selected as the dispersant because of its melting point of 1069°C. Specifically, the oxalate precursor was first annealed at 400°C for 3 hours to convert the oxalate to mixed oxide intermediates. The phases in the intermediates are confirmed by XRD. Despite poor crystallinity, the phases in the intermediates could be pointed to halite NiO, tenorite CuO, halite MgO, spinel Co3O4, and wurtzite ZnO. SEM and TEM images revealed that the bundle-like structure was preserved after moderate temperature annealing. Interestingly, the intermediate rods have a mesoporous structure. This is because the thermal decomposition of the oxalate precursor leaves substantial internal voids within these rods. The as-annealed intermediate was finely dispersed in K2SO4, followed by further annealing the mixture at 1000 °C for 3 h.
[0123] The XRD patterns in Figure 5 were prepared by solid-state dispersion-assisted annealing (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 )O high entropy oxide is a single phase compound with no impure phases. The peak positions are shown in Table 2 below. The Rietveld refinement results in FIG. 6 show good convergence and low R-factors, indicating that the (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2We confirm that the )O high entropy oxide has an fcc cubic crystal structure with the Fm3 m space group. The refined lattice parameters are a = 4.2395(3) Å, b = 4.2395(3) Å, c = 4.2395(3) Å, α = β = γ = 90°, and V = 76.199(8) Å. In such a structure, oxygen anions occupy the 4a sites, while the octahedral 4b sites are randomly co-occupied by Co, Cu, Ni, Zn, and Mg ions with a coordination number of 6. This is a specific example of a high entropy oxide that is an entropy stabilized oxide.
[0124] [Table 3]
[0125] Figure 7(a) shows the SEM image of the as-annealed high entropy oxide rods, which confirms that the uniformity and bundle-like structure of the oxalate precursor are preserved to a large extent after annealing. Unlike the porous intermediate, the high entropy oxide nanorods were quite dense, which is evidenced in the bright-field TEM image (Figure 7(b)). As shown in Figure 7(c), the high-resolution TEM image shows the (111) lattice fringes of the high entropy oxide with a lattice spacing of 0.246 nm. The axial (longitudinal) direction of the nano-sized rods is along the
[0111] axis. The corresponding fast Fourier transform (FFT) pattern is shown in the upper left corner. The EDS line scan across the width of the high entropy oxide rods showed that the distribution of the five cations in the high entropy oxide became more uniform across the rods when compared to the line scan results for the oxalate precursor.
[0126] Figure 8(a) shows an atomically resolved HAADF-STEM image of a high-entropy oxide nanorod projected along the
[0100] orientation. This image clearly reveals that the high-entropy oxide has an fcc sublattice of metal cations with oxygen anions residing in the octahedral cavities represented by four large spheres (Me) and 12 small spheres (O). Figure 8(b) shows an annular bright-field (ABF) image, which shows that the metal atomic columns are axially aligned with the O atomic columns along the
[0100] orientation. The ABF image along the
[0110] direction (Figure 8(d)) shows that some O anions show a slight drift from their perfect octahedral sites. This drift is due to the presence of tetrahedrally coordinated Cu anions in the octahedral arrangement. 2+ This is believed to arise from the distortion of the anion sublattice caused by the Jahn-Teller effect on
[0127] Example 3: (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 Electrochemical performance of )O high entropy oxides The resulting high entropy oxide was used to construct an electrochemical half-cell, in which a lithium disk was used as both the counter and reference electrodes.
[0128] FIG. 18 shows a schematic diagram of a half-cell in the form of a coin cell 1816, including a top cap 1802, a high entropy oxide working electrode (anode layer 1804), a polymer separator 1806, a counter electrode (lithium disk 1808), a stainless steel spacer 1810, an o-ring 1812, and a bottom cap 1814.
[0129] The anode layer 1804 was prepared by a typical slurry method. The high entropy oxide powder synthesized according to Example 2 was mixed with carbon black and PVDF binder to form a slurry with a mass ratio of 8:1:1 in N-methyl-2-pyrrolidinone (NMP). The resulting slurry was coated onto a copper foil. The thin film was then heated on a hot plate at 80°C to evaporate the NMP, followed by completely drying the thin film at 80°C overnight under vacuum. A CR2032 coin cell was constructed in a glove box under a pure argon atmosphere. In the coin cell 2-electrode configuration shown in Figure 18, a lithium disk 1808 was separated from the anode layer 1804 by a polymer separator 1806. The electrolyte (not shown) was 1 M LiPF6 dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a capacity ratio of 1:1. The mass loading of the active material on the anode layer 1804 was 0.924-1.052 mg / cm. 2 It was.
[0130] Figure 9(a) shows the current at 0.1 mV s -1 Cyclic voltammetry (CV) curves of the cell at a scan rate of 0.5 V are presented. The curves are similar to those of previously reported high entropy oxides (Sarkar et al.). The strong cathodic peak at 0.52 V significantly reduced after the first cycling, indicating solid electrolyte interface (SEI) formation and the initial reduction of the transition metal oxide to metal and Li2O. The slight cathodic peak at about 1.2 V during the first lithiation is due to the Cu 2+ / Cu + In the following cycles, four redox peaks are detectable from the CV results. A pair of strong redox peaks centered at 1.2 V (cathode) and 1.8 V (anode) can be attributed to the reduction of transition metal oxides and reoxidation of metals. In addition, a pair of minor redox peaks located at 0.375 V and 0.80 V can result from the combined effect of the alloying and dealloying process of Zn metal with Li and the spin-polarized surface capacitance of Co and Ni nanoparticles.
[0131] In previous studies (Sarkar et al. and Ghigna, P.; Airoldi, L.; Fracchia, M.; Callegari, D.; Anselmi-Tamburini, U.; D'Angelo, P.; Pianta, N.; Ruffo, R.; Cibin, G.; de Souza, DO; Quartarone, E., Lithiation Mechanism in High-Entropy Oxides as Anode Materials for Li-Ion Batteries: An Operando XAS Study. ACS Applied Materials & Interfaces 2020, 12 (45), 50344-50354), multiple additional cathodic peaks were commonly observed in the initial lithiation process, suggesting multiple individual lithiation reactions of the involved cations. Multiple cathodic peaks imply that known high-entropy oxide materials may still preserve small amounts of binary or ternary oxides in some microdomains. The CV curves for the subsequent cycles were almost identical after two cycles, indicating the excellent capacity retention of the high-entropy oxide electrode. Furthermore, the capacitance ranged from 0.3 to 1 mV s -1 The CV curves at increasing scan rates in Fig. 9(b) show similar redox trends, indicating good electrochemical responses to different charge-discharge rates.
[0132] Figure 9(c) shows the galvanostatic charge / discharge profiles of several representative cycles of the half-cell. The high-entropy oxide electrode discharged at 0.2 A g during the first cycle. -1 1639mAh g at a current of -1 The mechanism of lithium storage in high entropy oxides is a conversion-type reaction, so the first-time coulombic efficiency of the high entropy oxide anode only reaches 50.4%. Then, the lithiation capacity reaches 650 mAh g at the 30th cycle. -1 Then, at the 400th cycle, it dropped to 1170mAh g -1It is noteworthy that the voltage profiles of the 400th and 470th cycles are almost overlapping, indicating that the capacity of the high entropy oxide anode stabilizes after 400 cycles. Similarly, FIG. 10 shows the impressive cycling performance of the high entropy oxide anode, indicating that the high entropy oxide of the present invention is remarkably stable. Furthermore, the high entropy oxide anode exhibits excellent rate capability and impressive capacity retention at increasing charge / discharge rates (FIG. 11(a)). More specifically, the high entropy oxide anode provides high specific capacities of 545, 470, 407, and 308 mAh / g at 0.2, 0.5, 1, and 3 A / g, respectively. The capacity stabilizes at approximately 510 mAh / g post-cycle at 0.2 A / g, indicating the excellent structural stability of the high entropy oxide anode under electrochemical operating conditions. Figure 11(b) shows the charge / discharge profiles of the high entropy oxide anode at different charge / discharge rates. After fast cycling, the charge / discharge profile was 0.2 A g -1 The discharge profile at 0.2 A / g is overlaid in Figure 11(b), which appears to overlap with the discharge profile at 0.2 A / g prior to fast cycling from 1.5 to 1 V (dashed black line). Similarly, the discharge profile in the same range in Figure 9(c) shows minor changes in capacity with cycling, implying that this conversion reaction process is highly reversible.
[0133] The electrochemical performance of the high entropy oxide material prepared according to the present invention was compared with the corresponding material prepared using conventional annealing. The high entropy oxide particles obtained after conventional annealing were also assembled into half cells. Figure 11(c) shows the cycling performance of the conventionally annealed anode (CA-HEO) at a low charge-discharge rate of 0.1 A / g. Despite the low charge-discharge rate, the CA-HEO anode shows a sudden capacity degradation after 280 cycles. Furthermore, by comparing the first discharge profiles of both high entropy oxide anodes, the lithiation plateau observed in the high entropy oxide rod anode was lower than that of the CA-HEO anode, despite the similar discharge capacity. There is a potential difference of approximately 46.8 mV between the plateaus of the two high entropy oxide electrodes. Without being bound by theory, it is believed that this lithiation potential difference arises from the following two aspects: First, the wide particle size distribution of CA-HEO may result in non-uniform surface potential and kinetics of lithiation / delithiation. Second, the lithiation rate is determined by the crystallographic direction. The high entropy oxide rods synthesized in this study <111> The rods have an axial orientation of {110} and {112}, and the sidewall planes of the rods are {110} and {112}. These non-closely packed planes are kinetically favorable for lithiation. Although the fine size inevitably results in low initial coulombic efficiency (i.e., roughly 50%) due to the formation of a very large SEI, the short diffusion paths and stable 1D structure enable excellent long-term cycling and rate performance for the high-entropy oxide rod anodes.
[0134] The comparison of the high entropy oxide prepared by the present invention with two known high entropy oxide anodes is shown in Table 3. The high entropy oxide anode according to the present invention provides the most impressive electrochemical performance with the highest ratio of active material in the anode. Furthermore, it is believed that the low initial coulombic efficiency can be effectively overcome by various prelithiation methods.
[0135] [Table 4]
[0136] Example 4: Electrochemical Cell A coin cell 1902 containing a high entropy oxide anode was constructed with the high entropy oxide of Example 2. A schematic of the constructed coin cell 1902 is shown in FIG. 19. The coin cell 1902 included a top cap 1904, an anode 1906, a separator 1908, a cathode foil 1910, a stainless steel spacer 1912, a wave spring 1914, and a bottom cap 1916. The anode 1906 was (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zinc 0.2 )O high entropy oxide and was prepared by the slurry method described above in Example 3. The cathode foil 1910 comprised LiFePO4 or LiNiCoMnO2.
[0137] Example 5: Co-precipitation of oxalate precursors of (MgMnFeCoNi)O high entropy oxides Another high-entropy oxide ((MgMnFeCoNi)O, (Mg 0.2 Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 The oxalate precursor of 1,2-dichlorophenyl ether (O) was prepared using a method similar to that of Example 1. However, some of the divalent cations involved (i.e., Fe 2+ and Mn 2+ ) are vulnerable to oxygen due to their high tendency to be oxidized to their higher valence states. Therefore, the preparation of the precursor was carried out in an inert atmosphere using a Schlenk line so that a pure Ar (argon) environment could be used during the synthesis. The samples were prepared by first dissolving 0.1 mmol of ascorbic acid (C6H8O6) in a mixture of 15 ml of deionized H2O and 15 ml of ethylene glycol. Ascorbic acid, a reducing agent, reduces the amount of Fe in the aqueous solution. 2+ and Mn 2+It can effectively prevent the oxidation of metal ions. Then, 1.1 mmol of MgCl2 (98%), 1 mmol of MnCl2·4H2O (98%), 1 mmol of FeCl2 (98%), 1 mmol of CoCl2·6H2O (99%), and 1 mmol of NiCl2·6H2O (100%) were dissolved in the above solution in a round-bottom flask. After all metal chlorides were added to the solution, the flask was quickly connected to a Schlenk line and purged with argon gas three times. This solution of metal ions was warmed to 50°C with stirring. In another mixed solution of deionized H2O and ethylene glycol (15 ml + 15 ml), 5.1 mmol of ammonium oxalate monohydrate (NH4)2C2O4·H2O was dissolved at 50°C. The solution was then deoxygenated using a Schlenk line, after which it was injected into the solution of chlorides with vigorous stirring. After reacting at 50° C. for 6 hours, the oxalate precursor was washed and separated by centrifugation several times, followed by drying the precursor at 50° C. overnight.
[0138] FIG. 14 shows an SEM image of rod-shaped particles of the oxalate precursor, (MgMnFeCoNi)C2O4.
[0139] Example 6: Preparation of (MgMnFeCoNi)O high entropy oxide The (MgMnFeCoNi)O high entropy oxide as a single-phase solid solution was directly formed by calcining the oxalate precursor at high temperature. The precursor was calcined at 1000°C for 5 h in an Ar atmosphere using a tube furnace in a covered corundum ceramic boat. The precursor was placed in a quartz pan in the boat, and MnO2 as an oxygen generator was placed next to the quartz pan. The use of the quartz pan allowed the MnO2 to be located close to the precursor sample while preventing contact and contamination. The amount of precursor powder was 300 mg, and that of MnO2 was 90 mg. Maintaining a temperature of 1000°C for an extended period of at least 5 h was found to be an effective annealing process that resulted in high entropy oxide with good purity.
[0140] After formation, the high-entropy oxide was allowed to cool naturally, and the resulting dark brown powder was found to be stable at ambient room conditions, as the phase purity did not change after the sample was exposed to air for several weeks.
[0141] When the calcination and annealing process was carried out in a pure Ar atmosphere, without an oxygen source, the material thus obtained was found to contain a mixture of wustite (FeO) and Ni alloy (Figure 13(a)). The presence of metallic phases can be attributed to the generation of reduction by-products (i.e., carbon and carbon monoxide) due to the decomposition of the oxalate ligands during the heat treatment.
[0142] MnO2 was used in the calcination process as an oxygen generator to mitigate the effects of a reducing environment. MnO2 progressively decomposes at high temperatures, releasing small amounts of O2 to neutralize reductive materials or slightly oxidize as-formed metal products. The covered boat provided sufficient containment to maintain an oxidizing environment. MnO2 undergoes thermal decomposition as follows: (400℃~800℃)2MnO2=Mn2O3+1 / 2O2 (Over 800℃)Mn2O3=2Mn3O4+1 / 2O2
[0143] Figure 13(b)-(d) show the XRD patterns of the samples formed by the addition of MnO2 as an external oxygen source. The excess oxygen from the decomposition of MnO2 gives rise to the spinel product (AB2O4, A = Mg, Mn, Fe, Co, Ni; B = Fe, Mn) as shown in Figure 13(b). 2+ and Mn 2+ The ions are converted to Fe by the extra oxygen produced by the decomposition of MnO2. 3+ and Mn 3+ is proportionally oxidized to Fe, forming spinel ferrite. 3+ and Mn 3+ and the remaining divalent cations (Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ , and Ni 2+) results in a spinel product. These undesirable components can be avoided and / or minimized by utilizing an appropriate amount of oxygen introduced during the annealing process, which amount can be easily determined by simple testing.
[0144] FIG. 13(c) shows the coexistence of spinel and metal phases in the oxide product calcined at 1000° C. with controlled addition of MnO2 and annealed by maintaining at 1000° C. for 1 hour. Due to the limited oxygen diffusion rate in the fixed bed, insufficient annealing resulted in an over-oxidized top layer and an under-oxidized bottom layer. This issue was addressed by extending the annealing period. As shown in FIG. 13(d), when the calcined oxide was annealed by maintaining the same temperature with the same amount of MnO2, compared to the product in FIG. 13(c), an annealing time of 5 hours resulted in a well-crystallized single-phase solid solution with rock salt crystal structure. The peak positions are shown in Table 4.
[0145] [Table 5]
[0146] The oxidation state of each metal species was investigated by X-ray absorption near edge structure (XANES), and the results in FIG. 15 show that the four transition metal elements uniformly have an average state close to +2. The slight increase in pre-edge intensity for the FeO reference material is due to the FeO oxidation state, which has a tetrahedral geometry. 3+ Octahedrally coordinated Fe 2+ This can be attributed to slight oxidation of
[0147] Figure 16 shows an SEM image of the as-annealed high entropy oxide material. The SEM shows rod-shaped particles and some agglomeration between the particles. The use of solid-state dispersants, such as those described herein, reduces agglomeration. Figure 17(a) shows a dark-field scanning transmission electron microscopy (DF-STEM) analysis and Figures 17(b)-(f) show energy dispersive spectroscopy (EDS) mapping of the high entropy oxide particles. A uniform distribution of different metal species can be clearly observed within a representative (MgMnFeCoNi)O particle.
[0148] It is not intended that the scope of the present invention be limited solely to the above-described examples, as those skilled in the art will recognize that many variations are possible without departing from the scope of the present invention as set forth in the appended claims.
Claims
1. 1. A method for preparing a high entropy oxide, comprising the steps of: (a) mixing a solution comprising at least four elementally distinct metal cations in a solvent, each metal cation constituting at least 5% of the total number of said four or more elementally distinct metal cations, with a precipitating agent to obtain a solid material comprising said at least four metal cations; (b) heat treating the solid material to obtain a high entropy oxide; wherein the precipitating agent comprises an organic anion.
2. The method of claim 1 , wherein the heat treatment comprises a calcination process that produces a high entropy oxide intermediate.
3. The method of claim 2 , wherein the heat treatment comprises annealing the high entropy oxide intermediate to obtain the high entropy oxide.
4. The method of claim 3 , wherein the high entropy oxide intermediate is mixed with a solid-state dispersant prior to annealing.
5. The method of any one of claims 1 to 4, wherein the heat treatment comprises the use of a controlled atmosphere.
6. The method of any one of claims 1 to 5, wherein the solution comprises at least five elementally different metal cations.
7. 7. The method of any one of claims 1 to 6, wherein each metal cation is independently selected from the group consisting of cations of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb and Pt.
8. The method of any one of claims 1 to 7, wherein the metal cations are independently selected from the group consisting of cations of Mg, Co, Ni, Cu and Zn.
9. 9. The method of any one of claims 1 to 8, wherein the metal cations are independently selected from the group consisting of cations of Mg, Mn, Fe, Co and Ni.
10. The method according to any one of claims 1 to 9, wherein the precipitating agent is an oxalate compound.
11. The method of any one of claims 1 to 10, wherein the solvent comprises water and ethylene glycol.
12. 12. The method of claim 10 or 11, wherein the oxalate compound is ammonium oxalate.
13. 1. A method for preparing a high entropy oxide, comprising the steps of: (a) mixing a solution comprising at least four elementally distinct metal cations in a solvent, each metal cation constituting at least 5% of the total number of said four or more elementally distinct metal cations, with a precipitating agent to obtain a solid material comprising said at least four metal cations; (b) heat treating the solid material to obtain a high entropy oxide intermediate; (c) combining the high entropy oxide intermediate with a solid-state dispersant and annealing the high entropy oxide intermediate to form the high entropy oxide; A method comprising:
14. An oxalate salt comprising four or more elementally distinct metal cations, each metal cation constituting at least 5% of the total number of metal cations.
15. 15. The oxalate salt of claim 14, wherein each metal cation constitutes between 5% and 30% of the total number of metal cations.
16. 16. The oxalate salt of claim 14 or 15 in the form of particles comprising the four or more elementally different metal cations.
17. 17. The oxalate salt of any one of claims 14 to 16, wherein each metal cation is independently selected from the group consisting of cations of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb and Pt.
18. The oxalate salt according to any one of claims 14 to 17, comprising a rod-like particle shape.
19. 19. The oxalate salt of claim 18, wherein the particle has a length:width ratio of about 1:1.5 to about 1:3.
5.
20. Formula (A v B w C x D y E z ) C 2 O 4 20. The oxalate of any one of claims 14 to 19, represented by the formula: wherein v, w, x, y and z are each independently from about 0.05 to about 0.30, and A, B, C, D and E are each independently selected from the group consisting of cations of Be, Mg, Ca, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Gd, Pb and Pt.